2009
DOI: 10.1016/j.jhsa.2009.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Forearm Instability

Abstract: Forearm instability is a complex problem resulting from traumatic disruption of the forearm stabilizers: the radial head, the interosseous membrane, and the triangular fibrocartilage complex. Dissociation of the forearm unit is often underrecognized and therefore inadequately treated, leading to poor patient outcomes. The goals of this article are to impart an understanding of the forearm anatomy and the current concepts in the diagnosis and treatment options for this complicated problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 47 publications
0
28
0
3
Order By: Relevance
“…Essex-Lopresti lesions are often suspected following high-energy falls onto an outstretched hand, e.g. a fall from a height (Dodds et al 2008, Green and Zelouf 2009). However, in the literature, a varying degree of force has been said to be required to disrupt the triangular fibrocartilage complex, the interosseous ligament, and to fracture the radial head (Hotchkiss et al 1989, Wallace et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Essex-Lopresti lesions are often suspected following high-energy falls onto an outstretched hand, e.g. a fall from a height (Dodds et al 2008, Green and Zelouf 2009). However, in the literature, a varying degree of force has been said to be required to disrupt the triangular fibrocartilage complex, the interosseous ligament, and to fracture the radial head (Hotchkiss et al 1989, Wallace et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…11 When the IOM is damaged (Essex-Lopresti injury), proximal migration of the radial head occurs, and immobilization of the forearm for at least 6 to 8 weeks is recommended to allow torn ligaments to heal. 5,12 However, there is little evidence in the literature that IOM has the capacity to heal with mechanical integrity after prolonged immobilization, 13 and it is postulated that herniation of the anterior compartment muscles causes separation of the torn edges of an IOM and, thus, prevents anatomical healing.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the cause is still believed to be the application an axial load to a pronated forearm, as during a fall [11, 15, 29]. In 2003, McGinley et al [55] demonstrated that the pattern of injury by an axial load depends on the rotational position of the forearm; with the forearm pronated, the resultant injury may be a fracture of the radial head and lesions to the IM.…”
Section: Trauma Mechanisms Of Essex-lopresti Lesions and The Biomechamentioning
confidence: 99%
“…In addition, injuries to the forearm can have a relevant impact on the wounded individual. In addition to Galeazzi fracture, Monteggia fractures complete forearm fractures and solitary radial head fractures, the Essex-Lopresti injury is a condition of dramatic changes to the structures and the function of the forearm following axial trauma [22, 29, 36, 59]. This combination of radial head fracture, lesions of the interosseous membrane (IM) and lesions of the distal radio-ulnar joint (DRUJ) was first clinically described by Curr and Coe in 1946 [13].…”
Section: Introductionmentioning
confidence: 99%